KONDISI FISIK OPTIMAL UNTUK PEMAIN SEPAK BOLA REMAJA - M. Said Zainuddin; Arifuddin Usman; Juhanis Juhanis; Sudirman Sudirman; Iskandar Iskandar (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2025)
Abstract: This study aims to explore the physical characteristics of high-level young soccer players based on their playing positions. The research method employed a cross-sectional design, involving 123 young players (average age 15 years) across various positions: goalkeepers, defenders, midfielders, and forwards. Data were collected through a series of tests measuring speed (5m, 10m, 20m sprints), agility (505 agility test, K-Test), as well as aerobic and anaerobic capacity (Yo-Yo Intermittent Recovery Level 1, Repeated Sprint Ability). Multivariate analysis of variance (MANOVA) was used to analyze significant differences between positions. The results revealed significant differences (p < 0.01) in physical parameters based on playing positions. Midfielders demonstrated better performance in agility and fitness tests compared to goalkeepers. In conclusion, the physical characteristics of young players are significantly influenced by their playing positions, indicating that training programs should be tailored accordingly. Keywords: Physical condition, football, player's physique Abstrak: Penelitian ini bertujuan untuk mengeksplorasi karakteristik fisik pemain sepak bola muda tingkat tinggi berdasarkan posisi bermain. Metode penelitian menggunakan desain cross-sectional dengan melibatkan 123 pemain muda (rata-rata usia 15 tahun) dari berbagai posisi: penjaga gawang, bek, gelandang, dan penyerang. Data dikumpulkan melalui serangkaian tes yang mengukur kecepatan (sprint 5m, 10m, 20m), ketangkasan (agility 505, K-Test), serta kapasitas aerobik dan anaerobik (Yo-Yo Intermittent Recovery Level 1, Repeated Sprint Ability). Analisis varians multivariat (MANOVA) digunakan untuk menganalisis perbedaan signifikan antar posisi. Hasil penelitian menunjukkan perbedaan signifikan (p < 0.01) dalam parameter fisik berdasarkan posisi bermain. Pemain gelandang menunjukkan performa lebih baik dalam tes ketangkasan dan kebugaran dibandingkan penjaga gawang. Kesimpulannya, karakteristik fisik pemain muda sangat dipengaruhi oleh posisi bermain, sehingga program pelatihan perlu disesuaikan. Kata kunci: Kondisi fisik, sepakbola, fisik pemain